(untitled) (International Journal of Engineering and Computer Science, 2014)
It is known that exposure to loud noise for prolonged periods of times is dangerous and can affect quality of life with reference to health and psychology. In severe cases it may result in damage or permanent loss of hearing. Exposure to 85 dB noise for more than eight hours and 100 dB noise for more than two hours is considered to be dangerous for humans. We studied noise due to machinery in use with heavy industry and present finding and details on noise due to Transfer Press Machine used in forming of heavy metal sheets.